Diet in the Driving Seat: Natural Diet-Immunity-Microbiome Interactions in Wild Fish - Friberg, Ida M.; Taylor, Joe D.; Jackson, Joseph A. (Frontiers in Immunology, 2019)
Natural interactions between the diet, microbiome and immunity are largely unstudied. Here we employ wild three-spined sticklebacks as a model, combining field observations with complementary experimental manipulations of diet designed to mimic seasonal variation in the wild. We clearly demonstrate that season-specific diets are a powerful causal driver of major systemic immunophenotypic variation. This effect occurred largely independently of the bulk composition of the bacterial microbiome (which was also driven by season and diet) and of host condition, demonstrating neither of these, per se, constrain immune allocation in healthy individuals. Nonetheless, through observations in multiple anatomical compartments, differentially exposed to the direct effects of food and immunity, we found evidence of immune-driven control of bacterial community composition in mucus layers. This points to the interactive nature of the host-microbiome relationship, and is the first time, to our knowledge, that this causal chain (diet → immunity → microbiome) has been demonstrated in wild vertebrates. Microbiome effects on immunity were not excluded and, importantly, we identified outgrowth of potentially pathogenic bacteria (especially mycolic-acid producing corynebacteria) as a consequence of the more animal-protein-rich summertime diet. This may provide part of the ultimate explanation (and possibly a proximal cue) for the dramatic immune re-adjustments that we saw in response to diet change.